Religious Moderation in a Review of Practical Fiqh - Abdul Aziz (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Differences in religious views that often trigger conflict do not only occur between religious communities, but also occur within Muslims. One of the causes is the narrow interpretation and understanding of religious teachings. This research uses literature and conceptual studies. The values of moderation in fiqh thinking include always trying to minimize differences of opinion, being tolerant amidst differences of opinion, being careful ( ihtiyath ) in enforcing laws, and not being fanatical in madhhab. Religious moderation in practical fiqh refers to efforts to: 1. Find a balance between religious principles and the needs of society in solving practical problems in life; 2. Finding a balance between fiqh principles and the social and cultural context of society; and 3. Finding solutions that are in accordance with the principles of fiqh (Islamic law) in contemporary situations and conditions.